The domestic fowl (Gallus gallus domesticus) embryo as an alternative for mammalian experiments – Validation of a test method for the detection of endocrine disrupting chemicals. (April 2018) - Jessl, Luzie; Scheider, Jessica; Oehlmann, Jörg
Abstract: In recent decades the embryo of Gallus g. domesticus has been widely used as a model for the study of early sexual development and the potential impact of substances affecting development, including endocrine disrupting chemicals (EDCs). Since there is no standardized procedure available for experiments with the chicken embryo, the objective of our project is to expedite the protocol to assess the potential effects of EDCs on early sexual differentiation. The main aim of the present study was to systematically investigate the natural variability of individual developmental and histological key parameters in untreated and solvent-treated control groups, since this has been insufficiently addressed so far. A further aim was to provide robust values for all parameters investigated in control and substance experiments, using two known estrogenic compounds, bisphenol A (75/150/300 μg/g egg) and 17α-ethinylestradiol (20 ng/g egg). On embryonic day 1 eggs were injected with the estrogenic compounds. On embryonic day 19 histological gonadal data as well as morphological parameters were noted. In baseline experiments with control groups the selected endpoints showed reproducible results with low variabilities. Furthermore, gonadal endpoints responded sensitively to the treatment with the two model EDCs. Thus, these endpoints are recommended for the assessment of suspected EDCs in which the values provided for all parameters can serve as validity criteria in future experiments. The embryo of G. domesticus has shown to be a suitable alternative to currently accepted mammalian bioassays for the impact assessment of EDCs on reproductive tissues. Highlights: The first study to systematically examine the variability of individual parameters in control groups of chicken embryos. The low natural variability of the test system results in a good reproducibility in control and substance-treated groups. Reference values for developmental and gonadal endpoints, suggested as validity criteria, are provided. The chicken embryo is a suitable system for the detection of EDCs and a promising alternative to mammalian experiments.